Institutional Impediments to Voluntary Ethics Measurement Systems - Stovall, O. Scott (Journal of business ethics, 2006)
In this paper, we argue that calls for widespread implementation of ethics measurement systems would be better informed by institutional economic analysis. Specifically, we assert that proponents of such systems must first recognize and understand the institutions that potentially impede such efforts. We identify two potential institutional impediments to measuring ethics and social responsibility. First, we suggest that neoclassical economics, supported by traditional business education and legal precedent, serves to reinforce the notion that shareholders are the primary corporate constituency group. Such an emphasis on the needs of shareholders severely hinders implementation of measurement systems that address the needs of multiple stakeholder groups. Second, we argue that the threat of litigation may constrain corporate managers from measuring and considering ethics and corporate social responsibility matters. In particular, managers may be reluctant to quantify various ethical concerns if the resulting measurements could be used as evidence against the corporation in a lawsuit.